Promoting Psychological Resilience in Teens - Ritu, Ritu (Journal of Neonatal Surgery, 2025)
The majority of mental health challenges are diagnosed during teenage and young adult years. According to the National Alliance on Mental Illness, about 17% of youth ages 6-17 experiences a mental health disorder. When teens are coping with a mental health challenge, it can impact all aspects of their life including school, relationships, and even physical health. Adolescent mental health is an increasingly important area of concern, with rising rates of anxiety, depression, and stress-related issues. This study aims to evaluate the effectiveness of a structured mental health toolkit designed to improve emotional well-being and coping mechanisms among teenagers. Conducted over six weeks in a school-based setting, the toolkit included mindfulness activities, emotion regulation strategies, and peer support modules. Results indicated improvements in self-reported mental health parameters and enhanced emotional resilience. The findings suggest that a structured toolkit can be an effective early intervention method in adolescent mental health care